Extraction, purification, structural characterization, bioactivities, modifications and structure–activity relationship of polysaccharides from Ophiopogon japonicus: a review - Zhang, Yiqiang; Chen, Bo; Zhang, Hua; Zhang, Juan; Xue, Juan (Frontiers in Nutrition, 2024)
Ophiopogon japonicus (Thunb.) Ker Gawl., is a traditional Chinese medicine (TCM) with a history of thousands of years. O. japonicus polysaccharides (OJPs), as one of the main active ingredient, are a kind of representative pharmacological bioactive macromolecules and mainly composed of Glc and Fru with molecular weight between 2.48 kDa to 325 kDa. OJPs have a variety of biological activities, such as hypoglycemic, cardioprotective, immunomodulatory, improvement of obesity, and renal protective activity. In this review, the extraction, purification and structural characterization of OJPs were systematically reviewed, and its biological function, molecular mechanism and structure-activity relationship were analyzed.Additionally, this review summarized and found that structural modifications such as liposome modification, sulfation modification, and polyethylene glycol modification have improved the pharmacological activity and bioavailability of OJPs. Overall, this work will help to better understand OJPs and provide a theoretical review of their further development and utilization in the field of medicine and health food.